Analisis Pelaksanaan Pemusnahan Berkas Rekam Medis Rawat Jalan Di RS Khusus Mata SMEC Medan Tahun 2021 - Johanna Christy (Cybernetics: Journal Educational Research and Social Studies, 2021)
Inactive medical record files on storage shelves will not always be stored, because the number of medical records in hospitals continues to grow. Destruction of medical records is one of the efforts made by the hospital with the aim of reducing the accumulation of medical record files in the storage room. Special Eye Hospital SMEC Medan has 3 medical record officers. After 10 years, the Medan SMEC Hospital has retained medical record files in July 2021. And will carry out destruction. This study aims to determine how the preparation of human resources in the implementation of the destruction, the facilities used in the implementation of the destruction, and the assessment of inactive medical record files that will be destroyed. The type of research used is descriptive with a qualitative approach. The population in this study were all medical record officers at the Medan SMEC Eye Special Hospital in 2021. The method of data collection was using observation. In the results of the study conducted at the Special Eye Hospital, SMEC Medan, there were 6 medical record officers. One of the reasons for not carrying out the destruction is due to the unavailability of tools for the destruction of medical record files. The SMEC Medan Eye Special Hospital will only hold a retention in July 2021 to be exact on 5 July 2021. It is hoped that the Medan SMEC Eye Special Hospital will add human resources with medical record education, provide facilities in the form of tools to destroy medical record files, and carry out retention of medical record files. on time in accordance with the time set by the Director General of Yanmed.